ECONOMIC AND SOCIAL ANALYSIS BY THE TAXATION - Gomero Gonzales, Nicko Alberto (2016)
Taxes are applied by governments to finance government spending. The orientation of disbursements is based on public or fiscal policies, which –as it is known- their main function is to improve the social and economic gaps through effective redistribution. But for these redistributive policies to be effective, a basic condition is that economic growth is sustained and as a result of this, because of the work exerted by automated instruments, like taxes. Then, greater flows of budget revenues will be experienced. Over time, in Peru, the government revenues have only been based largely on two pillars; the tax on production, consumption and income, but with greater force tax flows have rested on VAT, a situation that leads to assert that the national tax system is essentially regressive. While income tax is below the VAT, its participation is relevant to finance the budget, especially those that are applied to corporate profits and personal income.